2011
DOI: 10.1073/pnas.1107941108
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvanticity of the oil-in-water emulsion MF59 is independent of Nlrp3 inflammasome but requires the adaptor protein MyD88

Abstract: Oil-in-water emulsions have been successfully used to increase the efficacy, immunogenicity, and cross-protection of human vaccines; however, their mechanism of action is still largely unknown. Nlrp3 inflammasome has been previously associated to the activity of alum, another adjuvant broadly used in human vaccines, and MyD88 adaptor protein is required for the adjuvanticity of most Toll-like receptor agonists. We compared the contribution of Nlrp3 and MyD88 to the adjuvanticity of alum, the oil-in-water emuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
129
2
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(141 citation statements)
references
References 32 publications
5
129
2
5
Order By: Relevance
“…A possible explanation for this finding is that with lupus-associated autoantigens, adjuvanticity is provided by endosomal TLR engagement by selfnucleic acids, whereas adjuvanticity of complete (CFA) and incomplete (IFA) Freund's adjuvants, or alum in response to conventional exogenous antigens is mediated by endosomal TLRindependent pathways (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this finding is that with lupus-associated autoantigens, adjuvanticity is provided by endosomal TLR engagement by selfnucleic acids, whereas adjuvanticity of complete (CFA) and incomplete (IFA) Freund's adjuvants, or alum in response to conventional exogenous antigens is mediated by endosomal TLRindependent pathways (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…These adjuvants stimulate local inflammatory responses at the injection site, which lead to leukocyte recruitment, antigen transport to draining lymph nodes, and APC activation (17). In preclinical models, adjuvants like MF59 appear to stimulate lymphocyte priming through a TLR-independent MyD88-dependent pathway (18) and subsequent Th2-mediated antibody responses (19), whereas the majority of helper CD4 T cells induced in people are biased to a Th0/Th1 phenotype (20,21). A separate strategy for inducing anti-viral Th1 responses involves activation of TLR4, which is unique among the TLR family in its ability to activate MyD88 and IFN production through the TRIF pathway (8).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that alum acts as an adjuvant to activate the intracellular stress sensor inflammasomes [28,29] and ROS are required for inflammasome activation [30]. However, the critical role of alum as an adjuvant to activate inflammasomes has been controversial, as alum can exert adjuvanticity also in mice deficient of inflammasomes [31,32]. A recent study revealed that alum-induced adjuvant effects are dependent on inducible heat shock protein 70 (hsp70) [33].…”
Section: Discussionmentioning
confidence: 99%